The effect of Arthrospira platensis capsules on CD4 T-Cells and antioxidative capacity in a randomized pilot study of adult women infected with human immunodeficiency virus not under HAART in Yaoundé, Cameroon - Winter, Frank Stéphane; Emakam, Francois; Kfutwah, Anfumbom; Hermann, Johannes; Azabji-Kenfack, Marcel; Krawinkel, Michael B.; Justus Liebig University Giessen (My University, 2014)
Dietary supplements are often used to improve the nutritional status of people living with HIV/AIDS (PLHIV). Arthrospira platensis (Asp), also known as Spirulina, is a cyanobacterium rich in proteins and micronutrients. Cell and animal trials described immune-modulating, antiretroviral and antioxidant activities. This pilot study describes the effects of the supplementation of 5 g/day of Asp on a pre-highly-active antiretroviral therapy (pre-HAART), HIV-infected, adult female population. It was conducted as a three-month randomized controlled trial (RCT) that compared a cup supplementation of five grams/day of Asp with a placebo of equal protein content and energy. The study included 73 HIV-infected women. The immediate outcome variables were CD4 T-cells, viral load and immune activation by CD8 T-cells expressing CD38. The antioxidant status was assessed by way of the total antioxidant capacity of the serum (TAOS). The renal function was documented by way of creatinine, urea and the calculated glomerular filtration rate. Statistical analyses were carried out with non-parametric tests, and the effect size of each interaction was calculated. No differences in the immunological and virological markers between the Asp and the placebo group could be observed. In the placebo group, 21 of 30 patients (70%) developed concomitant events, while in the Asp group, only 12 of 28 patients (43%) did. Both groups registered a significant weight increase; 0.5 kg (p < 0.05) in the Asp group and 0.65 kg (p < 0.05) in the placebo group. The antioxidant capacity increase of 56 (1 98) µM for Asp was significantly different from the decrease observed in the placebo group (p < 0.001). A slight increase in the creatinine level of 0.1 g/dL (p < 0.001) was observed in the Asp group, and no effect was observed in the urea levels. The improvement of the antioxidant capacity under Asp, shown for the first time on PLHIV, could become a focus for future research on the nutritional and health effects of Spirulina. The observed slight, but significant increase of serum creatinine needs further evaluation, especially with varying doses of Asp.
Keywords: HIV; pre-HAART; supplement; Spirulina; antioxidant; ddc:610